2017
DOI: 10.1097/bpo.0000000000000676
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes of Pediatric Elbow Dislocation—Risk Factors Associated With Morbidity

Abstract: Level IV-prognostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 19 publications
1
25
2
7
Order By: Relevance
“…We also found that the average immobilization period and the mean time to restore full ROM was longer in patients treated with K-wire. One study suggested that immobilization for over 2 weeks was associated with a statistically significant loss of range of motion [ 26 ], but, in our study, there was no difference in the proportion of patients with restoration of full ROM between the K-wire group and the screw group. This discrepancy may have resulted from the fact that all subjects in the present study had isolated medial epicondylar fractures without elbow dislocation.…”
Section: Discussioncontrasting
confidence: 86%
“…We also found that the average immobilization period and the mean time to restore full ROM was longer in patients treated with K-wire. One study suggested that immobilization for over 2 weeks was associated with a statistically significant loss of range of motion [ 26 ], but, in our study, there was no difference in the proportion of patients with restoration of full ROM between the K-wire group and the screw group. This discrepancy may have resulted from the fact that all subjects in the present study had isolated medial epicondylar fractures without elbow dislocation.…”
Section: Discussioncontrasting
confidence: 86%
“…Las luxaciones de codo representan el 3-6 % de todas las lesiones de codo en la población general; no obstante, es raro encontrarlas en los niños sin fracturas asociadas. 1,2 Debido a la inmadurez esquelética, el tejido óseo es más débil que el ligamentario, y, en consecuencia, un mayor estrés aplicado sobre el codo, habitualmente, resulta en una lesión ósea y no en una luxación aislada. 2,3 Tienen su pico de incidencia en la segunda década de la vida debido al cierre parcial del cartílago de crecimiento de los huesos que conforman el codo.…”
Section: Discussionunclassified
“…El codo es la articulación grande luxada con más frecuencia en los niños menores de 10 años. 1 No obstante, las luxaciones representan el 3-6 % de todas las lesiones del codo y son significativamente menos habituales que su fractura, 2,3 lo que hace que las luxaciones puras, sin fracturas asociadas, sean muy raras.…”
Section: Introductionunclassified
“…La evaluación radiográfica básica incluye imágenes anteroposterior y lateral del codo antes de la reducción y después, con la atención dirigida a fracturas asociadas, en especial, al epicóndilo medial que es la más frecuente (hasta el 50% de los casos). 5,6 Estudios previos indican que la luxación debe tratarse de inmediato o no más allá de las cuatro horas, con el paciente sedado y comprobación radiográfica. 1,5,6 casos clínIcos caso 1 Niño de 6 años, sin antecedentes clínicos, que se había caído de un árbol con el codo en hiperextensión.…”
Section: Idunclassified
“…5,6 Estudios previos indican que la luxación debe tratarse de inmediato o no más allá de las cuatro horas, con el paciente sedado y comprobación radiográfica. 1,5,6 casos clínIcos caso 1 Niño de 6 años, sin antecedentes clínicos, que se había caído de un árbol con el codo en hiperextensión. A las ocho horas de la caída, consultó en el Departamento de Urgencia con dolor y deformidad en el codo derecho.…”
Section: Idunclassified